Historical Narrative of Yesenin’s Poem “Pugachev” as Dialogue-Rivalry with Pushkin - S. N. Pyatkin (Tsentr nauchnykh i obrazovatelnykh proektov, 2017)
The article is devoted to historicism of Yesenin’s poem “Pugachev” (1921) in the light of A. S. Pushkin’s concept of national history, where there are his works in the foreground, united by “Pugachev’s” topic. The novelty of the research lies in the fact that the first attempt of understanding of polemical dialogue between Pushkin and Yesenin from the point of view of literary study was made, reflected in the idea of the “Pugachev” poem and determined the ideological and philosophical constructs of Yesenin’s historicism. Special attention is paid to the role of legend in historiosophical position of Pushkin and Yesenin, and their relationships with Christian axiology, and also to the place of Yesenin’s treatise “Maria’s Keys” in the artistic philosophy of its author, expressed in the dramatic poem “Pugachev.” It is concluded that Yesenin’s historical event becomes the auxiliary material for the creation of a new legend, by its values being out the principles of Pushkin’s historicism. The author argues that in a polemical dialogue between Pushkin and Yesenin, expressed in a declarative treatment of the later poet to one of the most important predecessor in ethical and artistic terms, one should see defence of his own positions in contemporary literature, typical for Yesenin’s works of these years.